2016
DOI: 10.1186/s13643-016-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-onset sepsis and its public health burden: a systematic review

Abstract: BackgroundSepsis is a life-threatening condition and major contributor to public health and economic burden in the industrialised world. The difficulties in accurate diagnosis lead to great variability in estimates of sepsis incidence. There has been even greater uncertainty regarding the incidence of and risk factors for community-onset sepsis (COS). We systematically reviewed the recent evidence on the incidence and risk factors of COS in high income countries (North America, Australasia, and North/Western E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 67 publications
1
13
0
3
Order By: Relevance
“…Our inclusion criteria were designed to detect community-onset sepsis cases. Nosocomial sepsis accounts for approximately 10% of total cases and carries a higher mortality than community-onset disease [ 21 ]. Therefore, we are likely to have underreported nosocomial cases of sepsis and consequently the true sepsis-associated mortality in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Our inclusion criteria were designed to detect community-onset sepsis cases. Nosocomial sepsis accounts for approximately 10% of total cases and carries a higher mortality than community-onset disease [ 21 ]. Therefore, we are likely to have underreported nosocomial cases of sepsis and consequently the true sepsis-associated mortality in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infections (BSIs) refer to various pathogenic microorganisms that have invaded the blood, primarily bacteria and fungi [1] . With the increasing number of invasive procedures and the unreasonable use of broadspectrum antibacterial drugs and corticosteroids, the incidence and mortality of BSIs increase annually, as has been reported in many studies [2,3] . For example, the incidence of BSIs increased by 64% from 945 to 1,546 per 100,000 hospitalized patients per year from 2000 to 2013 in a Swedish county, and the 30-day mortality of BSIs was up to 12.8% [4] .…”
Section: Introductionmentioning
confidence: 96%
“…Prior evidence suggests sex-related risk differences for developing sepsis. However, the prognostic effect of sex on sepsis outcomes remains uncertain, as previous studies reported inconsistent ndings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%